2009
DOI: 10.1073/pnas.0906094106
|View full text |Cite
|
Sign up to set email alerts
|

Frontoparietal white matter diffusion properties predict mental arithmetic skills in children

Abstract: Functional MRI studies of mental arithmetic consistently report blood oxygen level-dependent signals in the parietal and frontal regions. We tested whether white matter pathways connecting these regions are related to mental arithmetic ability by using diffusion tensor imaging (DTI) to measure these pathways in 28 children (age 10 -15 years, 14 girls) and assessing their mental arithmetic skills. For each child, we identified anatomically the anterior portion of the superior longitudinal fasciculus (aSLF), a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
107
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 43 publications
17
107
2
Order By: Relevance
“…Being one of the major fiber bundles connecting frontoparietal regions the SLF is likely implicated in high-order cognitive processing and increased FA values have been associated with verbal abilities (Tamnes et al, 2010;Gold, Powell, Xuan, Jiang, & Hardy, 2007) and arithmetic skills (Tsang et al, 2009) in regions corresponding to the left SLF. Further, a DTI study found verbal working memory performance in schizophrenia patients and healthy participants to be correlated with FA in left SLF (Karlsgodt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the major fiber bundles connecting frontoparietal regions the SLF is likely implicated in high-order cognitive processing and increased FA values have been associated with verbal abilities (Tamnes et al, 2010;Gold, Powell, Xuan, Jiang, & Hardy, 2007) and arithmetic skills (Tsang et al, 2009) in regions corresponding to the left SLF. Further, a DTI study found verbal working memory performance in schizophrenia patients and healthy participants to be correlated with FA in left SLF (Karlsgodt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This approach avoids the potential disadvantages of the voxel-based approaches, such as the need for larger sample sizes and artifacts caused by spatial normalization or smoothing techniques (Jones et al, 2005;Niogi et al, 2007), which often make it impossible to distinguish between differences in microstructure and those attributable to variability in gross anatomical shape and size. Regions were selected on the basis of a previous finding outlining the SCR as a key white matter region associated with general arithmetical abilities (van Eimeren et al, 2008) and the SLF having been previously associated with approximate but not exact arithmetic (Tsang et al, 2009).…”
Section: Dti Acquisition and Analysismentioning
confidence: 99%
“…In addition, FA values were also extracted from the left and the right SLF. As discussed above, the SLF has recently been associated with approximate but not exact arithmetic (Tsang et al, 2009) and thus provides another means to constrain the specificity of any relationships between the lSCR and activation of the lAG during exact calculation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…b) DDs show differences in connectivity among the relevant parietal regions, and between these parietal regions and occipito-temporal regions associated with processing symbolic number form (Rykhlevskaia, Uddin, Kondos, & Menon, 2009), in comparison with typically developing learners. This means that DD learners have not sufficiently developed the structural connections between brain regions that coordinate the components needed for calculation (Price & Ansari, 2012;Tsang, Dougherty, Deutsch, Wandell, & Ben-Shachar, 2009). …”
Section: The Consequences For Learnersmentioning
confidence: 99%